Estimating air volumetric flow rate of outdoor chemical plants for occupational health hazards assessment - Hassim, M. H. (Faculty of Chemical and Natural Resources Engineering, 2008)
Performing occupational health hazards assessment is a crucial task in all workplaces, especially in chemical industries. The assessment involves four steps of: hazard identification, toxicity assessment, exposure assessment, and risk characterization. Exposure assessment is the heart in health hazards evaluation. In determining worker's potential exposure, it is essential to estimate exposure concentrations. This can be accomplished if information on the chemicals emission rates and ventilation rates is available. In this paper a method to estimate air volumetric flow rates, Q, for outdoor facilities is proposed. The method was developed based on two variables; the wind speed and the area of the facility. The critical part of the method is to provide the estimates of areas of typical process modules in a chemical plant. Detailed but easy steps on how to perform the Q calculation are provided. The method was tested on six alternative processes to manufacture methyl methacrylate (MMA). For validation purpose, the results were then compared to the actual air flow rates required to maintain the acceptable exposure limits level in the plant. The results indicate that the Q values estimated using the proposed method were more than sufficient. However, bare in mind, the method gives only an estimate value, which is best used for early assessment purpose. The method is applicable to large petrochemical plants.